Pekanbaru Religious Court's Policy on the Implementation of Legal Litigation Legal Rights Besides Advocates - Robert Libra (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Regulations set by the Government provide guidance in formulating a policy in the Religious Court of Pekanbaru, in the implementation there is a policy that is felt beyond the regulations that may complicate the Legal Aid providers. Specific targets of this research are to provide suggestions for the Supreme Court in order to formulate the regulation of the Rights of Legal Aid Specialist in the Religious Court of Pekanbaru. The type of research is sociological law research. In the data collection used nonstructural interview, observation, and literature review. In this case, the result of Pekanbaru Religious Court Policy on the Implementation of Legal Litigation Legal Rights Besides Advocate as well as a policy on the rights that an advocate obtains when dealing with a professional case in a religious court. However, although legal aid providers other than advocates have been accepted and admitted to the newborn religious court, no legal aid providers other than advocates have come as good legal aid providers it's from paralegals, lecturers, or law faculty students who come to accompany the poor. The lack of socialization of legislation by the government on society has made people unaware that there are legal aid providers other than advocates. When filing a lawsuit / petition in a newbie religious court has additional rules regarding the filing of case registration as there are additional letters to be completed, namely letter of advocate appointment by LBH, letter of willingness of advocate, and letter of attendance of first session.